LYMPHOCYTE APOPTOSIS AND PROLIFERATIVE ACTIVITY IN PATIENTS WITH PULMONARY TUBERCULOSIS AND MULTIPLE DRUG RESISTANCE OF M. TUBERCULOSIS - E. G. Churina (SPb RAACI, 2014)
Abstract. The work concerned some parameters of proliferation and apoptosis in peripheral blood lymphocytes in patients with primary pulmonary tuberculosis (Tbc), as dependent on clinical form of the disease and sensitivity of M. tuberculosis to specific medical drugs. It was shown that, in patients with infiltrative and disseminated Tbc, as well as in cases of multi-drug resistance of M. tuberculosis, an increased apoptosis of lymphocytes is observed, accompanied by inhibition of their proliferative activity. The numbers of apoptotic and proliferating lymphocytes remain within normal ranges in patients with fibrous/cavernous form of the disease, and in cases of drug-sensitive M. tuberculosis.